A Model to Improve the Quality of E-Learning in Farhangian University of Khuzestan - Morid Niazi; Morteza Bakhtiarvand (Randwick International of Education and Linguistics Science Journal, 2020)
The aim of this study was to design a model to improve the quality of e-learning at Farhangian University of Khuzestan Province. For this research, the mixed research method of sequential exploratory type has been used. The statistical population of the research consists of a number of managers and officials of Farhangian University, experts, thinkers and prominent professors of this university. In the qualitative part of the research, sampling was done purposefully and in the quantitative part, the sampling method was stratified-random. The qualitative method of content analysis was used to construct the model and the quantitative descriptive-analytical method was used to test the model and the correlation type based on the structural equation model was used. The results of 15 interviews conducted, through open and axial coding (using Max QDA Pro version software), led to the extraction of 142 concept codes and 12 main categories, which are management and infrastructure, program Courses, objectives, content, educational media, social, cultural and moral factors, economic factors, human factors, interaction, teaching and learning, evaluation and homework and support infrastructure. Given that the T-value for 5 relationships related to the research hypotheses is more than 0.95, this means a good fit of the model.